2011
DOI: 10.1111/j.1468-3083.2011.04161.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of topical calcineurin inhibitors as monotherapy or in combination with hydroxychloroquine in cutaneous lupus erythematosus

Abstract: Topical calcineurin inhibitors enhance the therapeutic effect of systemic agents in cutaneous lupus erythematosus, and result in improvement of the clinical parameters studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Calcineurin, a serine‐threonine phosphatase, plays an important role in activating the nuclear factor of activated T cells, which binds to the promotor regions of various cytokines, such as interleukin (IL)‐2, tumour necrosis factor‐α, interferon‐γ, IL‐4 and IL‐10 . The topical CIs tacrolimus and pimecrolimus have been beneficial, as monotherapeutic agents, in several human CLE subtypes, suggesting that these agents may be a well tolerated and safer therapeutic option to topical glucocorticoids . The use of ciclosporin in human CLE has been the subject of only rare reports .…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin, a serine‐threonine phosphatase, plays an important role in activating the nuclear factor of activated T cells, which binds to the promotor regions of various cytokines, such as interleukin (IL)‐2, tumour necrosis factor‐α, interferon‐γ, IL‐4 and IL‐10 . The topical CIs tacrolimus and pimecrolimus have been beneficial, as monotherapeutic agents, in several human CLE subtypes, suggesting that these agents may be a well tolerated and safer therapeutic option to topical glucocorticoids . The use of ciclosporin in human CLE has been the subject of only rare reports .…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus 0.1% was found to be efficacious in a randomized, doubleblind, vehicle-controlled trial of 30 patients of CLE, especially in acute, edematous, non-hyperkeratotic lesions of CLE patients. [21] Wahie et al, [22] in their multicenter observational and pharmacology study, investigated the effects of disease attributes and metabolizing cytochrome P450 (CYP) polymorphisms on clinical outcome of DLE. Although the majority of patients responded to hydroxychloroquine, a significant proportion (39%) either failed to respond or were intolerant to the drug.…”
Section: Cutaneous Lupus Erythematosus and Cancermentioning
confidence: 99%
“…A study of 38 patients showed both tacrolimus and pimecrolimus to be effective in improving symptoms of erythema, desquamation, and edema, independent of disease type [37]. In a comparison between 0.1% tacrolimus and 0.05% clobetasol propionate ointments in 21 DLE patients, negative effects of tacrolimus were limited to transient pruritus and burning, whereas telangiectasia was observed in 61% of patients following clobetasol treatment.…”
Section: Pharmaceutical Interventionsmentioning
confidence: 99%